Comparative Proteomics Analysis of Serum Proteins in Gestational Diabetes during Early and Middle Stages of Pregnancy. Issue 5 (3rd July 2019) - Shen, Liming; Zhao, Danqing; Chen, Youjiao; Zhang, Kaoyuan; Chen, Xinqian; Lin, Jing; Li, Cuihua; Iqbal, Javed; Zhao, Yuxi; Liang, Yi; Wei, Yan; Feng, Chengyun
Abstract : Purpose: This study is designed to screen serum proteins that may serve as biomarkers for gestational diabetes mellitus (GDM), and clarify the mechanisms of disease. Experimental Design: By using isobaric tags for relative and absolute quantitation proteomics analysis, serum proteins levels were quantified in pregnant women who subsequently developed GDM (12–16 weeks), GDM patients (24–28 weeks), and their corresponding controls. The strategy of mixing samples is used in proteomic analysis. Results: Thirty‐one and 27 differentially expressed proteins are identified in the serum of pregnant women with developed GDM at 12–16 weeks and GDM patients during 24–28 weeks, respectively. Thirty eight and 28 proteins are identified in 24–28 weeks versus 12–16 weeks controls (24/12 CTR group), and 24–28 weeks GDM patients versus 12–16 weeks women with subsequently developed GDM (24/12 GDM group), respectively. Most of these proteins in the case and control subjects are associated with diabetes and maternal and perinatal short‐ and long‐term complications. Conclusions and Clinical Relevance: The results highlight the roles of complement system and the blood clotting cascade in the pathogenesis of GDM. Differentially expressed proteins may serve as potential biomarkers for GDM prediction and diagnosis in the future.